2000
DOI: 10.1007/s001470050298
|View full text |Cite
|
Sign up to set email alerts
|

General compliance after liver transplantation for alcoholic cirrhosis

Abstract: In recent years, alcoholic cirrhosis has been accepted as an indication for OLT, compliance of patients suffering from alcoholic cirrhosis is still under discussion, however. 118 patients who had undergone OLT for alcoholic cirrhosis were considered for analysis. The mean follow-up time of the study population was 53.7 +/- 38.9 months. Compliance was defined by 3 parameters: 1. Sobriety. Fifteen (13%) out of 118 recipients suffered an alcohol relapse during the observation period. There was no difference betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 14 publications
1
41
0
4
Order By: Relevance
“…Rothenhäusler/Ehrentraut/Kapfhammer/ Lang/Zachoval/Bilzer/Schelling/Gerbes OLT recipients documented a figure of 16% at a mean follow-up time of 53.7 months [65]. Given that OLT recipients with immunosuppressive concentrations in blood not within the target range were enrolled in our study, it is possible that the prevalence of full PTSD in OLT recipients may be similar to that observed in the study by Stukas et al [53].…”
Section: Discussionmentioning
confidence: 55%
“…Rothenhäusler/Ehrentraut/Kapfhammer/ Lang/Zachoval/Bilzer/Schelling/Gerbes OLT recipients documented a figure of 16% at a mean follow-up time of 53.7 months [65]. Given that OLT recipients with immunosuppressive concentrations in blood not within the target range were enrolled in our study, it is possible that the prevalence of full PTSD in OLT recipients may be similar to that observed in the study by Stukas et al [53].…”
Section: Discussionmentioning
confidence: 55%
“…Potential advantages of improved adherence and more consistent exposure with the extended release profile of tacrolimus QD (3)(4)(5)(6)(7) include a reduction in rejection and graft loss (8)(9)(10) on longer-term follow-up.…”
Section: Prograf (Astellas Pharma Europe Ltd Staines Uk; Hereafter mentioning
confidence: 99%
“…Immunosuppressant medication noncompliance seems higher (Յ23%) than previously reported in alcoholics (16%). 21 However, the 6 programs reporting some form of patient noncompliance found that transplantation outcomes were not 22 Drug interactions are theoretically possible because tacrolimus and cyclosporine, the most common immunosuppressants used in liver transplantation, as well as methadone and Levomethadyl acetate hydrochloride, use the cytochrome P-450 system (CYP3A4). 23,24 No program reported drug interactions, and we found no reports of significant clinical interaction in MEDLINE.…”
Section: Commentmentioning
confidence: 99%